Copper(I)‐Catalyzed [3+2] Cycloaddition/Ring‐Opening Rearrangement/[4+2] Cycloaddition/Aromatization Cascade: An Unprecedented Chemo‐ and Stereoselective Three Component Coupling of Sulfonyl Azide, Alkyne and N‐Arylidenepyridin‐2‐ amine to Pyrido[1, 2‐a]pyrimidin‐4‐imine. Issue 1 (23rd December 2012) - Namitharan, Kayambu; Pitchumani, Kasi
Abstract A novel synthetic protocol for the one‐pot chemo‐ and stereoselective construction of diversely functionalized pyrido[1, 2‐a]pyrimidin‐4‐imines via copper(I)‐catalyzed [3+2] cycloaddition/ring‐opening rearrangement/[4+2] cycloaddition/aromatization cascade of sulfonyl azides, alkynes and N‐arylidenepyridin‐2‐amines under mild reaction conditions is reported. In addition, the catalytic activity of copper(I)‐modified zeolite, a recyclable, heterogeneous catalyst is also investigated, which gives improved yield compared to its homogeneous equivalents.